Unsaturated Fatty Acid Mutants of Saccharomyces cerevisiae - Resnick, Michael A. (1966)
Resnick, Michael A. (University of California, Berkeley), and Robert K. Mortimer. Unsaturated fatty acid mutants of Saccharomyces cerevisiae. J. Bacteriol. 92:597–600. 1966.—The wild type of the yeast Saccharomyces cerevisiae does not require fatty acids or sterols for growth. Two types of lipid nutritional mutants have been induced in this organism. One of these classes of mutants requires an unsaturated fatty acid and is associated with a locus on chromosome VII. The other class of mutants needs either an unsaturated fatty acid or ergosterol for growth. Experiments involving identification and characterization of these mutants are presented.